Analysis of Willing to Pay Program on Rice Business Insurance in Karawang Regency - Suriani, Teni; Devita, Dewi; Putra S, Gemilang Ralfianandha; Risdawati, Risdawati; Puspitasari, Avisa Kemala (Operations Research: International Conference Series, 2021)
This study aims to determine the level of farmer participation in the Rice Farming Business Insurance (AUTP) program, and to determine the estimated willingness of farmers to pay the AUTP premium in Karawang Regency and the factors that influence it. The sample in this study amounted to 100 people taken from two villages from two sub-districts, namely Kutapohaci Village in Ciampel District and LemahKarya Village in Tempuran District. Farmers in Karawang Regency are willing to pay the AUTP premium. There are 44% of respondent farmers who are willing to pay the AUTP premium, the average value of the willingness to pay the AUTP premium is IDR 42,480/ha/planting season, which is greater than the value of the AUTP self-help premium set by the current government, which is IDR 36,000/ha/season planting, with a WTP value of IDR 42,480/ha/MT. Farmers hope that there will also be an increase in claim benefits to IDR 7.080.000. Based on multiple regression analysis, the factors that influence the farmer's Willingness to Pay (WTP) value on the AUTP program are the variables of education, land area, land status and income (at the real level). 5 percent). Meanwhile, based on the results of the logit analysis, it is known that the factors that can increase the chances of farmers participating in the AUTP program independently by paying the AUTP premium are the WTP value and income.